PENGARUH PENJUALAN OBAT SECARA DARING (APOTEK DARING) TERHADAP PENJUALAN APOTEK KONVENSIONAL DI KECAMATAN TANJUNG PRIOK KOTA JAKARTA UTARA - Indrawan, Andhika; Piter, Piter (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
In today's digital era, technology is advancing rapidly, and society is required to adapt and master it to remain competitive. The internet, in particular, plays a significant role in the advancement of businesses, including the healthcare sector. The ability to purchase medication online has made it more convenient for consumers, eliminating the need to visit traditional pharmacies. This shift has impacted conventional pharmacies, particularly in terms of revenue, as consumers increasingly opt for more practical and efficient purchasing methods. Conventional pharmacies operate as physical stores providing direct services on-site. However, online sales of pharmaceuticals are restricted to those with proper authorization from relevant authorities, such as Electronic Pharmacy System Providers (PSEF), pharmaceutical wholesalers, and pharmacies utilizing an Electronic System (PSE). PSEF entities are responsible for providing, managing, and operating the electronic pharmaceutical system, as well as monitoring, evaluating, and reporting regularly. Despite the positive effects of online sales on revenue growth and market expansion, many conventional pharmacies continue to rely on traditional record-keeping systems. According to data from the North Jakarta Health Office in 2023, there are 51 conventional pharmacies in Tanjung Priok District that still use traditional systems. This study aims to understand how online pharmaceutical sales impact the sales performance of conventional pharmacies in this region.This research employs a descriptive method with a quantitative approach. It focuses on analyzing the impact of online pharmaceutical sales on conventional pharmacies, covering aspects such as service quality, product availability, operational hours, and revenue. Data were collected using questionnaires distributed both physically and via Google Forms. The sample includes all 51 conventional pharmacies in Tanjung Priok District, selected using a saturated sampling technique. The findings reveal that online sales have a notable influence on conventional pharmacies, particularly regarding service enhancement, product availability, and operational adjustments.